Caminhos históricos sob o olhar de Rugendas: a ligação entre Rio de Janeiro e Minas Gerais - Patrícia Gomes da Silveira (Confins)
This article offers a historical-geographic narrative about an ancient Caminho Real do Ouro (Royal Road of Gold) – the Caminho do Proença. The main source for the construction of this narrative are the iconographic records of the German painter, Johann Moritz Rugendas. In the early 1820s, on his journey from Rio de Janeiro to Minas Gerais as an artist for the Langsdorff Expedition, Rugendas documented landscapes, nature, and territory along this path. Initially opened as gold drain route from the hinterlands of Minas Gerais through the port of Rio de Janeiro, the Caminho do Proença established itself as one of the main routes of circulation, settlement, and supply of this portion of the territory during the 18th century and in the first decades of the 19th century. Rugendas' iconography, together with other documentary sources, provides a rich historical record of the natural, economic, and urban aspects of this path between the coast of Rio de Janeiro and the sertões of Minas Gerais.